Stability and Accuracy of a Diagnosis of Parkinson Disease Over 10 Years - Räty, Valtteri; Kuusimäki, Tomi; Majuri, Joonas; Vahlberg, Tero; Gardberg, Maria; Noponen, Tommi; Seppänen, Marko; Tolppanen, Anna-Maija; Kaasinen, Valtteri (Ovid Technologies (Wolters Kluwer Health), 2025)
Background and objectives: Accurate diagnosis of Parkinson disease (PD) remains challenging, with variability and clinical uncertainty, especially in nonspecialized settings. Despite advancements in diagnostic criteria and biological markers, misdiagnosis continues to affect patient care and research. This study aimed to assess the long-term diagnostic stability of PD and evaluate the accuracy of initial diagnoses over time in a large, consecutive cohort diagnosed by neurologists, with or without movement disorder specialization.
Methods: We conducted a retrospective longitudinal analysis of patients diagnosed with PD between 2006 and 2020. Patient records were reviewed over a median follow-up period of 10 years, with more than half of the cohort tracked from motor symptom onset to death. Diagnostic evaluations included dopamine transporter (DAT) imaging and neuropathologic examinations for a subset of patients, based on clinical indications. Two movement disorder specialists cross-validated diagnoses through retrospective chart reviews.
Results: The cohort included 1,626 patients (mean age 69.0 years, 44.1% female). Of these, 10.6% (n = 172) had their diagnoses revised by treating neurologists, and 2.7% (n = 44) were revised based on chart reviews or neuropathologic findings. The median time to diagnosis revision was 22 months (interquartile range = 43). The most common revised diagnoses were vascular parkinsonism, progressive supranuclear palsy, and multiple system atrophy, with 4.7% (n = 77) classified as clinically undetermined parkinsonism. In a secondary analysis separating PD and dementia with Lewy bodies (DLB), the revision rate increased to 17.7%. DAT imaging had been performed on 588 patients and was more frequently used in revised cases. Postmortem neuropathologic examinations had been conducted in only 3% of deceased patients, with 64% confirming the initial PD diagnosis.
Discussion: This study demonstrates significant diagnostic instability in PD, with 13.3% of diagnoses revised, primarily within 2 years. When DLB is considered separately, the revision rate increases to 17.7%. Despite frequent DAT imaging and limited postmortem examinations, clinical uncertainty persists among practicing neurologists, contrasting with lower misdiagnosis rates in specialized centers. These findings highlight the need for systematic application of diagnostic criteria, regular reevaluation of diagnoses, more frequent autopsies, and the development of accessible diagnostic biomarkers.